Risk factors of necrotizing enterocolitis in very low birth weight infants: a meta-analysis - Bao, Liming; Huang, Jinyan (Frontiers in Pediatrics, 2026)
BackgroundThis study aims to explore the primary risk factors for necrotizing enterocolitis (NEC) in very low birth weight (VLBW) infants through meta-analysis, providing scientific evidence for clinical prevention and treatment.MethodsA systematic search was conducted in PubMed, Embase, Cochrane Library, and Web of Science databases for studies investigating risk factors for NEC in VLBW infants, covering the period from database inception to October 10, 2025. Eligible studies included case-control studies, cohort studies, and cross-sectional studies meeting the inclusion criteria. Quality assessment was performed using the NOS and AHRQ scores. Data were pooled using Stata 15 software with a random-effects model.Resultsa total of 16 research articles involving 179,289 patients included, meta-analysis results suggest that Small Gestational Age [OR = 1.35, 95% CI (1.14, 1.60)], red blood cells transfusion [OR = 1.75, 95% CI (1.26, 2.43)], maternal hypertensive disorders [OR = 1.27, 95% CI (1.03, 1.57)], patent ductus arteriosus [OR = 1.56, 95% CI (1.30, 1.88)], sepsis [OR = 1.87, 95% CI (1.22, 2.87)] were associated with NEC in very low birth weight infants.ConclusionThis systematic meta-analysis consolidates and confirms previously reported associations between several clinical factors and the risk of necrotizing enterocolitis in very low birth weight infants. The findings support the association of small gestational age, red blood cell transfusion, maternal hypertensive disorders, patent ductus arteriosus, and sepsis with an increased risk of NEC.Systematic Review RegistrationPROSPERO CRD420251149565.